THE IMPORTANCE OF USING MODERN TECHNOLOGIES IN TEACHING FINE ARTS AND DRAWING LESSONS - Rahmonova Dilafroz Ahrorovna; Fakhriddinov Muhammad Fakhriddivich (Journal Park Publishing, 2025)
This article discusses the importance of using modern technologies in art and drawing classes and the use of graphic programs to increase students' interest in science.
Keywords: Corel Draw, Photoshop, TURBOLOGO, Sketchbook, Canva, Auto Cad